Large bending deformations of pressurized curved tubes - Kolesnikov, A.M. (Archives of Mechanics, 2011)
In this paper, the problem of large pure bending deformations of membrane is considered. The membrane is a sector of torus with a closed cross-section. This membrane is called a curved tube for short. We consider the homogenous, incompressible, isotropic and hyperelastic material. The external load is a constant pressure and bending couples acting at the edges. The equilibrium equations reduce to ordinary differential equations. As an example, the membrane with a constant thickness and with a circular cross-section is investigated.